2016
DOI: 10.1016/j.epsl.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Strength of orthoenstatite single crystals at mantle pressure and temperature and comparison with olivine

Abstract: Orthoenstatite single-crystal plasticity is investigated at mantle P and T conditions Rheological laws for [001] dislocation slip in (100) and (010) planes are quantified OPx [001](100) slip system is weaker than [001](010) slip system at mantle conditions Olivine slip systems are weaker than OPx slip systems at most mantle conditions Olivine and OPx weak slip systems have comparable strength in the shallow lithosphere

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…For these low‐pressure experiments, the somewhat elongated grains perpendicular to the compression axis and the EBSD data suggest that dislocation creep takes place predominantly by activation of the (100)[001] slip system. As noted in Mackwell [] and Raterron et al [], this slip system is expected to be the easiest one under our experimental deformation conditions.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…For these low‐pressure experiments, the somewhat elongated grains perpendicular to the compression axis and the EBSD data suggest that dislocation creep takes place predominantly by activation of the (100)[001] slip system. As noted in Mackwell [] and Raterron et al [], this slip system is expected to be the easiest one under our experimental deformation conditions.…”
Section: Discussionsupporting
confidence: 54%
“…The addition of Al under dry conditions however yielded a CPO consistent with dominant activation of (010)[001]. Finally, Raterron et al [] observed that the enstatite (100)[001] slip system is also prevalent over the (010)[001] slip system at higher pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microstructures are often observed in samples deformed by a dislocation‐accommodated process in nature and experiment (e.g., Hansen et al, ; Linckens et al, ). In the pyroxene‐rich layers, the pyroxene grains form a weak texture with [010] approximately parallel to the Y direction (Figure b), an orientation typical of slip on the (100)[001] slip system in a sample deformed by dislocation creep, as observed in naturally and experimentally deformed orthopyroxene (e.g., Bystricky et al, ; Christensen & Lundquist, ; Raterron et al, ; Skemer et al, ). In contrast, as secondary phases (pyroxene in olivine‐rich aggregates and olivine in pyroxene‐rich aggregates), both phases show weak textures typical of uniform distributions (Figures d and e).…”
Section: Discussionmentioning
confidence: 86%
“…The dashed line is the best fit for data from Hansen et al (2012). Journal of Geophysical Research: Solid Earth 10.1002/2017JB014311 orthopyroxene (e.g., Bystricky et al, 2016;Christensen & Lundquist, 1982;Raterron et al, 2016;Skemer et al, 2006). In contrast, as secondary phases (pyroxene in olivine-rich aggregates and olivine in pyroxene-rich aggregates), both phases show weak textures typical of uniform distributions (Figures 9d and 9e).…”
Section: Development Of Crystallographic Fabricmentioning
confidence: 99%